Impacts of Cultural Identity Crisis on Self-Concept among Pakistani Young Adults - Isra Sarwar, (Journal of Peace, Development and Communication, 2023)
The present study aimed at exploring the lived experiences of young adults in Pakistan and the impacts of cultural identity crisis on their self-concept. Participants of the study comprised 8 university students (4 males; 4 females) ranging from 20-40 years in age; two participants (1 male; 1 female) from each province. Qualitative research was used and the sample was collected through a purposive sampling technique. Transcripts were analyzed by using interpretative phenomenological analysis (IPA). Four themes arose from the data, which are named cultural facets, ethnocentrism, cultural diffusion, and self-concept. Results revealed an understanding of the prevailing cultural identity crisis, and how it affects the self-concepts of adults. It was concluded that globalization, technology, and colonization are important contributing antecedents of the cultural identity crisis in Pakistan, which is ultimately affecting the self-concept of young adults. Future implications